Addressing anaemia in pregnancy in rural plains Nepal: A qualitative, formative study. (9th July 2021) - Morrison, Joanna; Giri, Romi; Arjyal, Abriti; Kharel, Chandani; Harris‐Fry, Helen; James, Philip; Baral, Sushil; Saville, Naomi; Hillman, Sara
Abstract: Maternal anaemia prevalence in low‐income countries is unacceptably high. Our research explored the individual‐, family‐ and community‐level factors affecting antenatal care uptake, iron folic acid (IFA) intake and consumption of micronutrient‐rich diets among pregnant women in the plains of Nepal. We discuss how these findings informed the development of a home visit and community mobilisation intervention to reduce anaemia in pregnancy. We used a qualitative methodology informed by the socio‐ecological framework, conducting semi‐structured interviews with recently pregnant women and key informants, and focus group discussions with mothers‐in‐law and fathers. We found that harmful gender norms restricted women's access to nutrient‐rich food, restricted their mobility and access to antenatal care. These norms also restricted fathers' role to that of the provider, as opposed to the caregiver. Pregnant women, mothers‐in‐law and fathers lacked awareness about iron‐rich foods and how to manage the side effects of IFA. Fathers lacked trust in government health facilities affecting access to care and trust in the efficacy of IFA. Our research informed interventions by (1) informing the development of intervention tools and training; (2) informing the intervention focus to engaging mothers‐in‐law and men to enable behaviour change; and (3) demonstrating the need to work in synergy across individual, family and community levels to address power and positionality, gender norms, trust in health services and harmful norms. Participatory groups and home visits will enable the development and implementation of feasible and acceptable strategies to address family and contextual issues generating knowledge and an enabling environment for behaviour change.